Analysis Of The Internal Control System Over Payroll And Wages At Pt.Roda Teknindo Purajayah - Agustin, Ayu; Wagini, Wagini; Hidayah, Nenden Restu (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
The payroll and wage accounting system needs to be carried out control activities to ensure that the implementation of the payroll and wage system runs according to established standards, including at PT. Roda Teknindo Purajaya. This company has implemented internal control over the payroll and wage system. The research objective is to determine the internal control system over the payroll and wage system at PT. Roda Teknindo Purajaya. This research includes comparative descriptive research, which describes the actual characteristics and conditions of a research object by comparing the internal control system over payroll and wages carried out at PT. Roda Teknindo Purajaya with Mulyadi's theory. Data is collected by documentation and interview methods, while data analysis uses comparative analysis. The results showed that the internal control system over payroll and wages at PT. Roda Teknindo Purajaya was in accordance with Mulyadi's theory. First organization, there has been a strict separation of functional responsibilities between the payroll maker function and the finance function. Second, the authorization system, the employee appointment letter is signed by the main director, in order to avoid paying salaries to fictitious employees, as well as changes in employee salaries, both due to changes in rank, changes in salary and wage rates, and additional families are always based on the director's decision letter. In addition to the separation of responsibilities, it is known that all documents used are always authorized by the authorized person. Third, the recording procedure has included salary and wage rates in the attendance card and is checked for accuracy by the bookkeeping department. Fourth, healthy practices, that supervision has been carried out, compared and verified against attendance cards and employee income tax calculations. Thus it can be conveyed that the internal control system over the payroll and wage system at PT. Roda Teknindo Purajaya is in accordance with the theory by Mulyadi.